(untitled) (مجلة الواحات للبحوث والدراسات, 2025)
This Study Aims To Shed Light On The Method And Method Of Evaluating The Performance Of Institutions, Considered Among The Most Important And Best Methods So Far In Evaluating The Performance Of Institutions, And Try To Drop Them On The Reality Of Evaluating The Performance Of Algerian University Education Institutions, Which Define A New Dynamic In Its Management, Especially With The Adoption Of Modern Means And Technologies Of Communication In Universities And Digitization In Their Pedagogical And Administrative Dealings And Their Goal To Reach Global Rankings In This Area, And Therefore Had To Adopt The Latest Methods And Methods In Measuring And Evaluating Their Performance. The Bibliographic Description Was Used To Define The Concepts And Terms Of The Study, And The Adoption Of The Questionnaire Method And Its Analysis By The Statistical Program For Human Sciences Spss25 For A Sample Of Directors And Managers Of Ghardaia University Consisting Of 60 Individuals, 43 Valid Forms Were Approved For Analysis, Through Which We Came To Realize That There Is Awareness Of The Dimensions And The Pillars Of The Application Of The Balanced Performance Card In Evaluating The University’s Performance And Applying The Financial Dimension And After The Internal Operations In The Evaluation, But There Is A Clear Deficiency In Linking These Dimensions With The University’s General Strategy Key Words - Performance; Evaluating Performance; Balanced Scorecard; Universities